César Vallejo and the Stones of Darwinian Risk - Christiane von Buelow (Studies in 20th & 21st Century Literature, 1990)
César Vallejo's short story, "Los caynas" (1923), relates a tale of species mutation, of men who become apes. The story, however, is something more than the reflection of the positivist interpretation of Darwinian theory. It can be read as a critique of Positivism's pseudo-scientific ideals or as a version of the Oedipal drama in which the son encounters and rejects his ape father. The ambivalence raises the question of whether Vallejo's Darwinism is to be read literally or ironically as well, as marking an antinomy present throughout his writing between the human subject's immersion in the species and the possibility of a collective human-transformation.
Keywords: César Vallejo; Los caynas; Darminism; evolution; positivist interpretation; Darwinian theory; Oedipal drama; Peruvian literature; short story